Shape-dependent adjuvanticity of nanoparticle-conjugated RNA adjuvants for intranasal inactivated influenza vaccines. Issue 30 (4th May 2018) - Tazaki, Taiyu; Tabata, Koshiro; Ainai, Akira; Ohara, Yuki; Kobayashi, Shintaro; Ninomiya, Takafumi; Orba, Yasuko; Mitomo, Hideyuki; Nakano, Tetsuo; Hasegawa, Hideki; Ijiro, Kuniharu; Sawa, Hirofumi; et al.
Abstract : Conjugation with gold nanorods enhanced the adjuvanticity of RNA adjuvant for intranasal inactivated influenza vaccines, providing efficient protection against infection in mice. Abstract : Intranasal inactivated influenza vaccines can elicit mucosal immune responses that protect against virus infection. For the development of intranasal inactivated influenza vaccines, effective adjuvants inducing minimal adverse reactions are required. Generally, however, lower toxicity adjuvants have lower adjuvanticity. In this research, we fabricated nanoparticle-based adjuvants to enhance its adjuvanticity. Herein, we focused on low-molecular-weight polyinosinic-polycytidylic acid, referred to as uPIC(40:400), as a weak and less toxic RNA adjuvant. We conjugated uPIC(40:400) with different shaped gold nanoparticles (AuNPs) electrostatically. Conjugation with gold nanorods, but not spherical AuNPs, markedly enhanced the adjuvanticity of uPIC(40:400), leading to the suppression of viral infection in mice. Notably, conjugation with gold nanorods did not increase the inflammatory cytokine production in dendritic cells. These data indicated that gold nanorods can provide a good platform for enhancing the weak adjuvanticity of uPIC(40:400) while maintaining low inflammatory cytokine production toward the development of intranasal inactivated influenza vaccines.